STUDI EMPIRIS PENGAMBILAN KEPUTUSAN INVESTASI INVESTOR KOTA MALANG PADA MASA PANDEMI COVID-19 - Qushoyyi, Fadhiil Dzakwan (Ma Chung Press, 2022)
The purpose of this study was to examine the effect of Anchoring, Representativeness, Availability and Overconfidence on Decision Making. Respondents in this study were Indonesian Capital Market Investors in Malang City. Respondents in this study amounted to 55 respondents. This study use the Multiple Linear Regression test tool. The results of this study indicate that Anchoring, Representativeness and Availability have no significant effect on Investor Decision Making in Malang City. Meanwhile, overconfidence has a significant effect on investors' decision making in Malang City. This study shows that there are several heuristic variables that do not affect investor decisions caused by other dimensional factors. Another dimension factor that causes differences in the results of empirical evidence is in Culture and Knowledge Sharing. In the context of Culture, each region has different characteristics of individual behavior. Knowledge Sharing as a factor also has a role in influence individual characteristics at decision making. Each individual has diversity and different level of knowledge sharing depending on the individual's ability to understand the knowledge obtained.